Twice electric field poling for engineering multiperiodic Hex-PPLN microstructures. (May 2018) - Pagliarulo, Vito; Gennari, Oriella; Rega, Romina; Mecozzi, Laura; Grilli, Simonetta; Ferraro, Pietro
Highlights: The use of Twice Electric Field Poling (TEFP) process is applied on a z-cut lithium niobate substrate. We have experimentally investigated the formation of HePPLN structures by interference microscopy in digital holography (DH) modality. These multi-periodic structures have been employed also to pattern liquid polymer such as PDMS. The reported results demonstrate the possibility of fabricating multi-periodic structures by simple multiple subsequent electric poling processes. Abstract: Satellite bulk ferroelectric domains were observed everywhere around the larger main inverted ferroelectric domains when a Twice Electric Field Poling (TEFP) process is applied on a z-cut lithium niobate substrate. TEFP approach can be very advantageous for engineering multiperiodic poled microstructures in ferroelectrics. In fact, it is very difficult in the experimental practice to avoid underpoling and/or overpoling when structures with different sizes are requested in the same crystal. TEFP was applied to photoresist patterned crystal with 100 µm period and then a second EP step, with a ten-times smaller periodicity of 10 µm, was accomplished on the same sample. The intriguing fact is that the shorter 10 µm pattern disappeared everywhere except that around the larger satellite ferroelectric domains. The formation of this double-periodicity in the reversed ferroelectric domains occurs very easily and in repeatedly way. We have experimentally investigated the formation of such HePPLN structures by an interference microscopy in digital holography (DH) modality. The reported results demonstrate the possibility of fabricating multi-periodic structures and open the way to investigate the possibility to achieve hierarchical PPLN structures by multiple subsequent electric poling processes.